GAMBARAN DERAJAT KEPARAHAN GEJALA PASIEN RINOSINUSITIS KRONIK DI RSUD DR. SOETOMO SURABAYA - Samara, Anggita Putri; Sutikno, Budi; I’tishom, Reny (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Chronic rhinosinusitis (CRS) is a sinus paranasal and nasal inflammation marked with two or more symptoms, nasal congestion or nasal discharge and the other symptom like facial pain and reduced smell may present. This symptom occur >12 weeks. One of the parameter for symptom’s severity assessmentis using Visual Analog Scale (VAS) that can be classified as mild (0-3), moderate (4-7), dan severe (8-10). This study was a observational study by assessing patient’s medical record at SMF THT-KL RSUD Dr. Soetomo and analyzed descriptively. 43 patients were enrolled to study (28 male and 15 female), most of them were between age 36-45 years old (25,58%). Most of the patient’s symptom’s severity in general, nasal obstruction, nasal discharge, facial pain, and reduced smell were moderate (65,11%), moderate (58,13%), mild (41,86%), mild (58,13%), mild (62,79%) respectively. Most of the patients had risk factor (62,79%), and the most of the patient’s risk factor were allergy. Most of the CRS patients in this study were male, 36-45 years old, with the general symptom’s severity moderate, moderate nasal obstruction, mild nasal discharge, mild facial pain, mild reduced smell, and had allergy.